School museum: A practical pedagogical experience In the study of geography with children (Revista Contexto & Educação, 2025)
This text presents considerations about the museum experience in school practice for the study of Geography with children in the early years of Elementary School. It presents records on the responsibilities of museums, with a view to preserving and preserving the memory of the facts of situations that made up the history of a given territory and its people, in collections of objects with historical and artistic value for society. It addresses theoretical aspects about the museum-school relationship, in the study of Geography and brings elements that help in the process of understanding the articulation in methodological practices that involve museum spaces, in the process of students' educational training. It records aspects of the experience of building, organizing and socializing the museum in the school environment, whose purpose is the study of Geography, through integrative activities with students. It is a proposal that changes the school's routine and corroborates by streamlining the teacher's pedagogical practice, by adopting methodological strategies that involve student participation in the construction of systematized geographic knowledge.
Keywords: School museum; Teaching Geography; Elementary School